A quantitative analysis 0f word-final /r/-deletion in Brazilian Portugese - Cardoso, Walcir (Linguistica Atlantica, 1999)
This study provides a quantitative analysis for the process of word-final /r/-deletion in the dialect of Portuguese spoken in the city of Belem, in northern Brazil. Two linguistic and four extralinguistic factors are considered in the investigation, all of which have a significant effect on the outcome of the process. Within the framework of Optimality Theory (Prince & Smolensky 1993), I propose an analysis for the general variation patterns found in /r/-deletion, along the lines of Reynolds (1994) and Anttila (1997).